Stochastic analysis proceedings of the Durham Symposium on Stochastic Analysis, 1990 - Barlow, M. T.; Bingham, N. H. (Cambridge University Press, 1991)
Durham Symposia traditionally constitute an excellent survey of recent developments in many areas of mathematics. The Symposium on stochastic analysis, which took place at the University of Durham in July 1990, was no exception. This volume is edited by the organizers of the Symposium, and contains papers contributed by leading specialists in diverse areas of probability theory and stochastic processes. Of particular note are the papers by David Aldous, Harry Kesten and Alain-Sol Sznitman, all of which are based upon short courses of invited lectures. Researchers into the varied facets of stochastic analysis will find that these proceedings are an essential purchase.